Phage treatment of an aortic graft infected with Pseudomonas aeruginosa. Issue 1 (8th March 2018) - Chan, Benjamin K; Turner, Paul E; Kim, Samuel; Mojibian, Hamid R; Elefteriades, John A; Narayan, Deepak
Abstract: Management of prosthetic vascular graft infections caused by Pseudomonas aeruginosa can be a significant challenge to clinicians. These infections often do not resolve with antibiotic therapy alone due to antibiotic resistance/tolerance by bacteria, poor ability of antibiotics to permeate/reduce biofilms and/or other factors. Bacteriophage OMKO1 binding to efflux pump proteins in P. aeruginosa was consistent with an evolutionary trade-off: wildtype bacteria were killed by phage whereas evolution of phage-resistance led to increased antibiotic sensitivity. However, phage clinical-use has not been demonstrated. Here, we present a case report detailing therapeutic application of phage OMKO1 to treat a chronic P. aeruginosa infection of an aortic Dacron graft with associated aorto-cutaneous fistula. Following a single application of phage OMKO1 and ceftazidime, the infection appeared to resolve with no signs of recurrence.